Pengaruh Ketepatan Waktu, Kualitas Pelayanan, Keamanan Dan Harga Terhadap Kepuasan Pelanggan J&T Express Lowokwaru Kota Malang (Studi Kasus Pada Mahasiswa Universitas Islam Malang) - Winardianto Hadi Susilah; Rois Arifin; Kartika Rose Rachmadi (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
AbstractThis study aims to tetst and explain the effect timelines, service quality, safety and price to satisfaction customers of J&T Express Lowokwaru Malang City case study on students University Of islam. This study uses a quantitative approach which uses the maholtra formula in order to determine the population is still not know with certainy, looking at the results of calculating the formula maholtra get the results of the number of samples of ninety. To complete the problems in this study use SPSS assistance in analyzing various kinds of tests were performed such as validity test, reliability test, test normality, classical assumption test, hypothesis test, multiple liniear regression test and test coefficient of determination adjusted R2 . The results of this study are timeliness, quality of service, security and price affect simultaneously on customer satisfaction and service quality and price are significant for customer satisfaction while timeliness and security are not significant to customer satisfaction. Keywords: Timeliness, Service Quality, Security, Price, Customer Satisfaction